An antibacterial high-strength BOPP film and preparation method thereof

By mixing cinnamaldehyde and Magnolol modified nanosilica with polypropylene resin, an antibacterial high-strength BOPP film was prepared by using a bidirectional stretching process, which solved the problem of difficulty in taking into account both the antibacterial effect and strength in the prior art, and achieved efficient sterilization and high-strength film materials.

CN119101303BActive Publication Date: 2025-04-11GUANGDONG XINJINTIAN COLOR PRINTING IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411383252.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-11
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing antibacterial BOPP films are difficult to improve the strength of the film while improving the antibacterial effect.

Method used

Antibacterial high-strength BOPP films were prepared by mixing cinnamaldehyde modified nanosilicon dioxide and magnolol modified nanosilicon dioxide with polypropylene resin.

Benefits of technology

It has achieved excellent antibacterial properties and high strength of BOPP films, can effectively sterilize and significantly improve mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119101303B_ABST
    Figure CN119101303B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of thin films, and discloses an antibacterial high-strength BOPP film and a preparation method thereof. The present invention uses magnolol and mercaptopropyl triethoxysilane modified nano-silica as raw materials, and after reaction, magnolol modified nano-silica is obtained. With tris (2-aminoethyl) amine, cinnamaldehyde, chloropropyl triethoxysilane modified nano-silica, etc. as raw materials, after reaction, cinnamaldehyde modified nano-silica is obtained, cinnamaldehyde modified nano-silica and magnolol modified nano-silica are added to polypropylene resin, mixed uniformly, extruded granulation, cast molding, heated and stretched, and antibacterial high-strength BOPP film is obtained. The present invention utilizes the antibacterial effect of magnolol, cinnamaldehyde, and quaternary ammonium salt, introduces them into BOPP film, can improve the antibacterial effect of film, utilizes rigid nano-silica to improve the strength of BOPP film, and it is confirmed by experiment that the BOPP film prepared by the present invention has excellent bactericidal performance and high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of films, in particular to an antibacterial high-strength BOPP film and a preparation method thereof. Background Art

[0002] In recent years, with the improvement of people's living standards and the enhancement of hygiene awareness, the demand for various antibacterial plastic products has continued to increase. Biaxially oriented polypropylene (BOPP) film is a film material with excellent performance that is made of polypropylene and processed by the biaxial stretching method. It is widely used in the preparation of people's daily necessities. Therefore, the research on the antibacterial modification of BOPP is a hot topic in the field of antibacterial research.

[0003] Cinnamaldehyde is a natural plant essential oil with excellent physiological activities, such as antibacterial and antiviral properties, but its volatility and oxidation seriously limit its application in medicine, food and agricultural production. Magnolia is a red bisphenol lignin that exists in different parts of natural magnolia plants. It has excellent antioxidant, antibacterial and anti-inflammatory properties and is widely used.

[0004] For example, the patent with authorization announcement number CN 102276910 B discloses an antibacterial polypropylene biaxially oriented film and a preparation method thereof. The invention uses polyguanidine / polysilicate as a composite antibacterial agent and adds it to a polypropylene resin. The prepared polypropylene biaxially oriented film has excellent antibacterial effect, and the antibacterial rate can reach 99.9%, but the strength of the polypropylene biaxially oriented film is not improved. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the deficiencies in the prior art, the present invention provides an antibacterial high-strength BOPP film and a preparation method thereof. The prepared BOPP film has excellent antibacterial properties and strength.

[0007] (II) Technical solution

[0008] An antibacterial high-strength BOPP film, the antibacterial high-strength BOPP film is composed of the following weight components: 100 parts by weight of polypropylene resin, 0.1-1 parts by weight of cinnamaldehyde modified nano-silica, and 0.1-1 parts by weight of magnolol modified nano-silica;

[0009] The preparation method of the antibacterial high-strength BOPP film is:

[0010] Cinnamaldehyde-modified nano-silica, magnolol-modified nano-silica and polypropylene resin are mixed evenly, placed in a drying oven at 80°C for 6-10 hours, taken out and extruded into granules using a twin-screw extruder, and cast into a standard sample; the standard sample is placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching to form a film, thereby obtaining an antibacterial high-strength BOPP film.

[0011] Preferably, the temperature of each zone of the extruder is 175°C, 185°C, 195°C, 200°C, and 240°C.

[0012] Preferably, the preheating temperature of the tensile testing machine is 160° C., the stretching temperature is 155° C., the stretching ratio is 5×5, and the stretching rate is 300% / s.

[0013] Preferably, the preparation method of the magnolol-modified nano-silica is:

[0014] Under nitrogen protection, magnolol and mercaptopropyl triethoxysilane modified nano-silica were added to dichloromethane solvent and stirred evenly, and benzoin dimethyl ether was added thereto. Under dark conditions, the solution was irradiated with 40W, 352nm ultraviolet light for 30-60min. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol modified nano-silica.

[0015] Preferably, the mass ratio of magnolol to mercaptopropyltriethoxysilane modified nano-silica is 1:1.8-2.4.

[0016] Preferably, the amount of benzoin dimethyl ether used is 2-5% of the total mass of magnolol and mercaptopropyltriethoxysilane modified nano-silica.

[0017] Preferably, the preparation method of the cinnamaldehyde modified nano-silica is:

[0018] S1, adding tri(2-aminoethyl)amine and potassium hydroxide to an ethanol solvent, stirring to dissolve, then adding cinnamaldehyde thereto, reacting at 50-65° C. for 3-6 hours, cooling after the reaction, filtering, washing with ether, and drying to obtain an intermediate product 1;

[0019] S2. Add the intermediate product 1, chloropropyltriethoxysilane-modified nano-silica and potassium iodide into ethanol solvent, stir and disperse, heat to 60-70°C, place in a microwave reactor, react for 10-15 hours, and after the reaction is completed, cool, stand and separate the liquids, rotary evaporate, wash with deionized water, and dry to obtain cinnamaldehyde-modified nano-silica.

[0020] Preferably, in S1, the mass ratio of tris(2-aminoethyl)amine, potassium hydroxide and cinnamaldehyde is 1:1-1.5:2.6-3.2.

[0021] Preferably, in S2, the mass ratio of the intermediate product 1, chloropropyltriethoxysilane-modified nano-silica, and potassium iodide is 1:0.5-0.8:0.01-0.03.

[0022] (III) Beneficial technical effects

[0023] The invention uses magnolol and mercaptopropyl triethoxysilane modified nano-silica as raw materials, and obtains magnolol modified nano-silica through a click reaction under the catalysis of benzoin dimethyl ether and ultraviolet light. Uses tris(2-aminoethyl)amine, cinnamaldehyde, chloropropyl triethoxysilane modified nano-silica and the like as raw materials, and obtains cinnamaldehyde modified nano-silica through a Schiff base reaction and a quaternization reaction. Finally, the cinnamaldehyde modified nano-silica and magnolol modified nano-silica are added to a polypropylene resin, mixed evenly, extruded into granules, cast into a film, and heated and stretched to obtain an antibacterial high-strength BOPP film.

[0024] The BOPP film prepared by the present invention not only contains green and environmentally friendly magnolol and cinnamaldehyde, but also contains a quaternary ammonium salt structure, all of which have relatively excellent antibacterial effects. Adding them to the BOPP film can assist each other and synergistically enhance the antibacterial effect of the BOPP film.

[0025] Since nano-silica itself is easy to agglomerate, the present invention reacts it with magnolol and cinnamaldehyde, which can not only reduce the volatilization degree of cinnamaldehyde, but also increase the dispersion degree of nano-silica, so that it can be evenly dispersed in the BOPP film. When subjected to external force, the rigid nano-silica particles can play a role in evenly distributing the load, thereby improving the strength of the BOPP film. The BOPP film prepared by the present invention has the characteristics of excellent high-efficiency sterilization, green safety, and high strength, and can be widely used. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the reaction process of magnolol modifying nano-silica;

[0027] Figure 2 This is the reaction process of cinnamaldehyde modifying nano-silica. DETAILED DESCRIPTION

[0028] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0029] Preparation of mercaptopropyl triethoxysilane modified nano-silica: add 10g of nano-silica to 67% mass fraction of ethanol aqueous solution, ultrasonically disperse, use 10% hydrochloric acid aqueous solution to adjust the pH to 4, add 2g of mercaptopropyl triethoxysilane, heat to 80°C, react for 12h, after the reaction is completed, cool to room temperature, filter, wash, and dry to obtain mercaptopropyl triethoxysilane modified nano-silica.

[0030] Preparation of chloropropyltriethoxysilane-modified nano-silica: Add 6 g of nano-silica and chloropropyltriethoxysilane into toluene solvent, stir and disperse, heat to 120° C., stir and react for 12 hours, and after the reaction, wash with deionized water and dry to obtain chloropropyltriethoxysilane-modified nano-silica.

[0031] Example 1

[0032] (1) Under nitrogen protection, 13.3 g of magnolol and 24.8 g of mercaptopropyl triethoxysilane-modified nano-silica were added to a dichloromethane solvent and stirred evenly. 2.3 g of benzoin dimethyl ether was added thereto. Under dark conditions, the solution was irradiated with 40 W, 352 nm ultraviolet light for 40 min. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol-modified nano-silica.

[0033] (2) 15 g of tris(2-aminoethyl)amine and 18 g of potassium hydroxide were added to an ethanol solvent and stirred to dissolve. Then, 40 g of cinnamaldehyde was added thereto and reacted at 60° C. for 5 h. After the reaction was completed, the mixture was cooled, filtered, washed with ether, and dried to obtain an intermediate product 1.

[0034] (3) 24 g of the intermediate product 1, 14 g of chloropropyltriethoxysilane-modified nano-silica, and 0.5 g of potassium iodide were added to an ethanol solvent, stirred and dispersed, heated to 65° C., placed in a microwave reactor, and reacted for 12 h. After the reaction was completed, the mixture was cooled, allowed to stand for separation, rotary evaporated, washed with deionized water, and dried to obtain cinnamaldehyde-modified nano-silica.

[0035] (4) 0.1 g of cinnamaldehyde-modified nano-silica, 0.1 g of magnolol-modified nano-silica and 100 g of polypropylene resin were mixed evenly, placed in a drying oven at 80°C for drying for 10 h, taken out and extruded into granules using a twin-screw extruder, and cast into standard samples, wherein the temperatures of each zone of the extruder were 175°C, 185°C, 195°C, 200°C, and 240°C. The standard samples were placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching to form a film, wherein the preheating temperature of the tensile testing machine was 160°C, the stretching temperature was 155°C, the stretching ratio was 5×5, and the stretching rate was 300% / s, to obtain an antibacterial high-strength BOPP film.

[0036] Example 2

[0037] (1) Under nitrogen protection, 13.3 g of magnolol and 30 g of mercaptopropyl triethoxysilane-modified nano-silica were added to a dichloromethane solvent and stirred evenly. 1 g of benzoin dimethyl ether was added thereto. Under dark conditions, the solution was irradiated with 40 W, 352 nm ultraviolet light for 30 min. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol-modified nano-silica.

[0038] (2) 15 g of tris(2-aminoethyl)amine and 18 g of potassium hydroxide were added to an ethanol solvent and stirred to dissolve. Then, 42 g of cinnamaldehyde was added thereto and reacted at 65° C. for 5 h. After the reaction was completed, the mixture was cooled, filtered, washed with ether, and dried to obtain an intermediate product 1.

[0039] (3) 24 g of the intermediate product 1, 15 g of chloropropyltriethoxysilane-modified nano-silica, and 0.4 g of potassium iodide were added to an ethanol solvent, stirred and dispersed, heated to 65° C., placed in a microwave reactor, and reacted for 14 h. After the reaction was completed, the mixture was cooled, allowed to stand for separation, rotary evaporated, washed with deionized water, and dried to obtain cinnamaldehyde-modified nano-silica.

[0040] (4) 0.4 g of cinnamaldehyde-modified nano-silica, 0.4 g of magnolol-modified nano-silica and 100 g of polypropylene resin were mixed evenly, placed in a drying oven at 80°C for drying for 6 h, taken out and extruded into granules using a twin-screw extruder, and cast into standard samples, wherein the temperatures of each zone of the extruder were 175°C, 185°C, 195°C, 200°C, and 240°C. The standard samples were placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching to form a film, wherein the preheating temperature of the tensile testing machine was 160°C, the stretching temperature was 155°C, the stretching ratio was 5×5, and the stretching rate was 300% / s, to obtain an antibacterial high-strength BOPP film.

[0041] Example 3

[0042] (1) Under nitrogen protection, 13.3 g of magnolol and 33 g of mercaptopropyl triethoxysilane-modified nano-silica were added to a dichloromethane solvent and stirred evenly. 0.75 g of benzoin dimethyl ether was added thereto. Under dark conditions, the solution was irradiated with 40 W, 352 nm ultraviolet light for 60 min. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol-modified nano-silica.

[0043] (2) 15 g of tris(2-aminoethyl)amine and 15 g of potassium hydroxide were added to an ethanol solvent and stirred to dissolve. Then, 40 g of cinnamaldehyde was added thereto and reacted at 55° C. for 5 h. After the reaction was completed, the mixture was cooled, filtered, washed with ether, and dried to obtain an intermediate product 1.

[0044] (3) 24 g of the intermediate product 1, 19.2 g of chloropropyltriethoxysilane-modified nano-silica, and 0.72 g of potassium iodide were added to an ethanol solvent, stirred and dispersed, heated to 60° C., placed in a microwave reactor, and reacted for 15 h. After the reaction was completed, the mixture was cooled, allowed to stand for separation, rotary evaporated, washed with deionized water, and dried to obtain cinnamaldehyde-modified nano-silica.

[0045] (4) 0.5 g of cinnamaldehyde-modified nano-silica, 0.6 g of magnolol-modified nano-silica and 100 g of polypropylene resin were mixed evenly, placed in a drying oven at 80°C for drying for 8 h, taken out and extruded into granules using a twin-screw extruder, and cast into standard samples, wherein the temperatures of each zone of the extruder were 175°C, 185°C, 195°C, 200°C, and 240°C. The standard samples were placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching to form a film, wherein the preheating temperature of the tensile testing machine was 160°C, the stretching temperature was 155°C, the stretching ratio was 5×5, and the stretching rate was 300% / s, to obtain an antibacterial high-strength BOPP film.

[0046] Example 4

[0047] (1) Under nitrogen protection, 13.3 g of magnolol and 26 g of mercaptopropyl triethoxysilane-modified nano-silica were added to a dichloromethane solvent and stirred evenly. 2 g of benzoin dimethyl ether was added thereto. Under dark conditions, the solution was irradiated with 40 W, 352 nm ultraviolet light for 50 min. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol-modified nano-silica.

[0048] (2) 15 g of tris(2-aminoethyl)amine and 20 g of potassium hydroxide were added to an ethanol solvent and stirred to dissolve. Then, 48 g of cinnamaldehyde was added thereto and reacted at 50° C. for 6 h. After the reaction was completed, the mixture was cooled, filtered, washed with ether, and dried to obtain an intermediate product 1.

[0049] (3) 24 g of the intermediate product 1, 12 g of chloropropyltriethoxysilane-modified nano-silica, and 0.24 g of potassium iodide were added to an ethanol solvent, stirred and dispersed, heated to 70° C., placed in a microwave reactor, and reacted for 10 h. After the reaction was completed, the mixture was cooled, allowed to stand for separation, rotary evaporated, washed with deionized water, and dried to obtain cinnamaldehyde-modified nano-silica.

[0050] (4) 0.8 g of cinnamaldehyde-modified nano-silica, 0.8 g of magnolol-modified nano-silica and 100 g of polypropylene resin were mixed evenly, placed in a drying oven at 80°C for drying for 8 h, taken out and extruded into granules using a twin-screw extruder, and cast into a standard sample, wherein the temperatures of each zone of the extruder were 175°C, 185°C, 195°C, 200°C, and 240°C. The standard sample was placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching to form a film, wherein the preheating temperature of the tensile testing machine was 160°C, the stretching temperature was 155°C, the stretching ratio was 5×5, and the stretching rate was 300% / s, to obtain an antibacterial high-strength BOPP film.

[0051] Example 5

[0052] (1) Under nitrogen protection, 13.3 g of magnolol and 30 g of mercaptopropyl triethoxysilane-modified nano-silica were added to a dichloromethane solvent and stirred evenly. 1.5 g of benzoin dimethyl ether was added thereto. Under dark conditions, the solution was irradiated with 40 W, 352 nm ultraviolet light for 50 min. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol-modified nano-silica.

[0053] (2) 15 g of tris(2-aminoethyl)amine and 22.5 g of potassium hydroxide were added to an ethanol solvent and stirred to dissolve. Then, 39 g of cinnamaldehyde was added thereto and reacted at 65° C. for 3 h. After the reaction was completed, the mixture was cooled, filtered, washed with ether, and dried to obtain an intermediate product 1.

[0054] (3) 24 g of the intermediate product 1, 14 g of chloropropyltriethoxysilane-modified nano-silica, and 0.5 g of potassium iodide were added to an ethanol solvent, stirred and dispersed, heated to 65° C., placed in a microwave reactor, and reacted for 12 h. After the reaction was completed, the mixture was cooled, allowed to stand for separation, rotary evaporated, washed with deionized water, and dried to obtain cinnamaldehyde-modified nano-silica.

[0055] (4) 1 g of cinnamaldehyde-modified nano-silica, 1 g of magnolol-modified nano-silica and 100 g of polypropylene resin were mixed evenly, placed in a drying oven at 80°C for drying for 10 h, taken out and extruded into granules using a twin-screw extruder, and cast into standard samples, wherein the temperatures of each zone of the extruder were 175°C, 185°C, 195°C, 200°C, and 240°C. The standard samples were placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching to form a film, wherein the preheating temperature of the tensile testing machine was 160°C, the stretching temperature was 155°C, the stretching ratio was 5×5, and the stretching rate was 300% / s, to obtain an antibacterial high-strength BOPP film.

[0056] Comparative Example 1

[0057] The antibacterial high-strength BOPP film and its preparation method provided in this comparative example are substantially the same as those in Example 1, with the main difference being that step (4) does not contain cinnamaldehyde-modified nano-silica.

[0058] Comparative Example 2

[0059] The antibacterial high-strength BOPP film and its preparation method provided in this comparative example are substantially the same as those in Example 1, with the main difference being that step (4) does not contain magnolol-modified nano-silica.

[0060] Comparative Example 3

[0061] The antibacterial high-strength BOPP film and its preparation method provided in this comparative example are substantially the same as those in Example 1, with the main difference being that step (4) does not contain magnolol-modified nano-silica and cinnamaldehyde-modified nano-silica.

[0062] Referring to QB / T2591-2003, the antibacterial properties of BOPP film were tested, and the test bacteria were Escherichia coli and Staphylococcus aureus.

[0063] Table 1: Antibacterial performance test results of various embodiments and comparative examples

[0064]

[0065] It can be seen from the table that the BOPP film prepared by the present invention has excellent antibacterial properties, and the maximum antibacterial rate against Escherichia coli and Staphylococcus aureus can reach 99.9%.

[0066] Referring to GB13022-91, a universal tensile testing machine was used to test the strength at a tensile rate of 200 mm / min.

[0067] Table 2: Mechanical properties test results of various embodiments and comparative examples

[0068]

[0069]

[0070] It can be seen from the table that the BOPP film prepared by the present invention has excellent mechanical properties. Combined with the data of Comparative Example 1, it can be seen that the mechanical properties of the BOPP film can be increased after adding nano-silicon dioxide.

[0071] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. An antibacterial high-strength BOPP film, characterized in that: The antibacterial high-strength BOPP film is composed of the following weight components: 100 parts by weight of polypropylene resin, 0.1-1 parts by weight of cinnamaldehyde-modified nano-silica, and 0.1-1 parts by weight of magnolol-modified nano-silica; The preparation method of the antibacterial high-strength BOPP film is: The cinnamaldehyde-modified nano-silica and magnolol-modified nano-silica were mixed evenly with polypropylene resin, placed in a drying oven at 80°C for 6-10 hours, taken out and extruded into granules using a twin-screw extruder, cast and formed into standard samples; the standard samples were placed in the stretching fixture of a film biaxial tensile testing machine for heating and stretching, and formed into films to obtain antibacterial high-strength BOPP films; The preparation method of the magnolol-modified nano-silica is: Under nitrogen protection, magnolol and mercaptopropyl triethoxysilane modified nano-silica were added to a dichloromethane solvent, stirred evenly, benzoin dimethyl ether was added thereto, and the solution was irradiated with 40W, 352nm ultraviolet light for 30-60min under dark conditions. After the reaction was completed, the solution was rotary evaporated, washed with deionized water, and dried to obtain magnolol modified nano-silica; The preparation method of the cinnamaldehyde modified nano silicon dioxide is: S1, adding tri(2-aminoethyl)amine and potassium hydroxide to an ethanol solvent, stirring to dissolve, then adding cinnamaldehyde thereto, reacting at 50-65° C. for 3-6 hours, cooling after the reaction, filtering, washing with ether, and drying to obtain an intermediate product 1; S2. Add the intermediate product 1, chloropropyltriethoxysilane-modified nano-silica and potassium iodide into ethanol solvent, stir and disperse, heat to 60-70°C, place in a microwave reactor, react for 10-15 hours, and after the reaction is completed, cool, stand and separate the liquids, rotary evaporate, wash with deionized water, and dry to obtain cinnamaldehyde-modified nano-silica.

2. The antibacterial high-strength BOPP film according to claim 1, characterized in that: The temperatures of the extruder zones are 175°C, 185°C, 195°C, 200°C, and 240°C.

3. The antibacterial high-strength BOPP film according to claim 1, characterized in that: The preheating temperature of the tensile testing machine is 160° C., the stretching temperature is 155° C., the stretching ratio is 5×5, and the stretching rate is 300% / s.

4. The antibacterial high-strength BOPP film according to claim 1, characterized in that: The mass ratio of magnolol to mercaptopropyltriethoxysilane modified nano-silica is 1:1.8-2.

4.

5. The antibacterial high-strength BOPP film according to claim 1, characterized in that: The usage of the benzoin dimethyl ether is 2-5% of the total mass of magnolol and mercaptopropyl triethoxysilane modified nano silicon dioxide.

6. The antibacterial high-strength BOPP film according to claim 1, characterized in that: In the S1, the mass ratio of tri(2-aminoethyl)amine, potassium hydroxide and cinnamaldehyde is 1:1-1.5:2.6-3.

2.

7. The antibacterial high-strength BOPP film according to claim 1, characterized in that: In S2, the mass ratio of the intermediate product 1, chloropropyltriethoxysilane-modified nano-silica, and potassium iodide is 1:0.5-0.8:0.01-0.03.

Citation Information

Patent Citations

  • Antibacterial polypropylene bidirectional stretching film and preparation method thereof

    CN102276910B

  • Quaternary ammonium salt functionalized nano-SiO2 antibacterial modified polypropylene material and preparation method thereof

    CN114044978A

  • Hydrophobic antibacterial PE preservative film, preparation method thereof and application of hydrophobic antibacterial PE preservative film in litchi preservation

    CN116948230A